2020
DOI: 10.1093/fs/knaa144
|View full text |Cite
|
Sign up to set email alerts
|

État présent: Dark Heritage

Abstract: Jérémie Dres's 2011 graphic novel, Nous n'irons pas voir Auschwitz, recounts a road trip taken by the author with his brother to explore their Polish-Jewish roots. 1 For Paris-born Dres, the idea of going to Auschwitz seemed deplorable not simply because of its reputation as a 'dark' tourist destination but also because the aim of the trip was to discover places associated with the lives of his great-grandparents, not their deaths. What their visits to Warsaw and elsewhere in Poland show is the way in which Je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For instance, Saha and Yap (2014) revealed that because people are inquisitive by nature, tourism demand tends to increase up to a threshold following terrorism incidents in nations with low to moderate political risk. Furthermore, global terrorism has generated a new and unique dimension to tourism on the so-called "dark side" of the tourism spectrum (Stone, 2012, p. 1), referred to as dark tourism (Lennon & Foley, 2000;Stone, 2006;Strange & Kempa, 2003), morbid tourism (Stone, 2012), atrocity heritage tourism (Kang et al, 2012), thanatological framework and thanatourism (Light, 2017;Stone & Sharpley, 2008), grief tourism (Lewis, 2008), sacred memorial sites (Podoshen & Hunt, 2011), popular shrine/altar and ritual space (Iliev, 2020), from lieux de mémoire to noeuds de mémoire (Fuggle, 2020), victimhoodscape or thanatoptic/dark heritage (Hooper & Lennon, 2016), and anamnesis tourism (Seaton, 2002). This paradigm has a common denominator of the aforementioned themes, which integrates them to assign the basis for a common thread for dark tourism.…”
Section: Review Of Global Security Threats and The Tandt Economymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Saha and Yap (2014) revealed that because people are inquisitive by nature, tourism demand tends to increase up to a threshold following terrorism incidents in nations with low to moderate political risk. Furthermore, global terrorism has generated a new and unique dimension to tourism on the so-called "dark side" of the tourism spectrum (Stone, 2012, p. 1), referred to as dark tourism (Lennon & Foley, 2000;Stone, 2006;Strange & Kempa, 2003), morbid tourism (Stone, 2012), atrocity heritage tourism (Kang et al, 2012), thanatological framework and thanatourism (Light, 2017;Stone & Sharpley, 2008), grief tourism (Lewis, 2008), sacred memorial sites (Podoshen & Hunt, 2011), popular shrine/altar and ritual space (Iliev, 2020), from lieux de mémoire to noeuds de mémoire (Fuggle, 2020), victimhoodscape or thanatoptic/dark heritage (Hooper & Lennon, 2016), and anamnesis tourism (Seaton, 2002). This paradigm has a common denominator of the aforementioned themes, which integrates them to assign the basis for a common thread for dark tourism.…”
Section: Review Of Global Security Threats and The Tandt Economymentioning
confidence: 99%
“…R. Stone, 2006;Strange & Kempa, 2003), morbid tourism (P. R. Stone, 2012), atrocity heritage tourism (Kang et al, 2012), thanatological framework and thanatourism (Light, 2017;P. Stone & Sharpley, 2008), grief tourism (Lewis, 2008), sacred memorial sites (Podoshen & Hunt, 2011), popular shrine/altar and ritual space (Iliev, 2020), from lieux de me´moire to noeuds de me´moire (Fuggle, 2020), victimhoodscape or thanatoptic/ dark heritage (Hooper & Lennon, 2016), and anamnesis tourism (Seaton, 2002). This paradigm has a common denominator of the aforementioned themes, which integrates them to assign the basis for a common thread for dark tourism.…”
Section: Review Of Global Security Threats and The Tandt Economymentioning
confidence: 99%